Implementation of the PIERS on the Move mHealth Application From the Perspective of Community Health Workers and Nurses in Rural Mozambique - Boene, Helena; Valá, Anifa; Kinshella, Mai-Lei Woo; La, Michelle; Sharma, Sumedha; Vidler, Marianne; Magee, Laura A.; von Dadelszen, Peter; Sevene, Esperança; Munguambe, Khátia; Payne, Beth A.; , the CLIP Mozambique Working Group (Frontiers in Global Women's Health, 2021)
Background: mHealth is increasingly regarded as having the potential to support service delivery by health workers in low-resource settings. PIERS on the Move (POM) is a mobile health application developed to support community health workers identification and management of women at risk of adverse outcomes from pre-eclampsia. The objective of this study was to evaluate the impact of using POM in Mozambique on community health care workers’ knowledge and self-efficacy related to caring for women with pre-eclampsia, and their perception of usefulness of the tool to inform implementation. Method: An evaluation was conducted for health care workers in the Mozambique Community Level Intervention for Pre-eclampsia (CLIP) cluster randomized trial from 2014-2016 in Maputo and Gaza provinces (NCT01911494). A structured survey was designed using themes from the Technology Acceptance Model, which describes the likelihood of adopting the technology based on perceived usefulness and perceived ease of use. Surveys were conducted in Portuguese and translated verbatim to English for analysis. Preliminary analysis of open-ended responses was conducted to develop a coding framework for full qualitative analysis, which was completed using NVivo12 (QSR International, Melbourne, Australia). Results: Overall, 118 community health workers (44 intervention; 74 control) and 55 nurses (23 intervention; 32 control) were surveyed regarding their experiences. Many community health workers found the POM app easy to use (80%; 35/44), useful in guiding their activities (68%; 30/44) and pregnant women received their counselling more seriously because of the POM app (75%; 33/44). Community health workers reported increases in knowledge about pre-eclampsia and other pregnancy complications and increases in confidence, comfort and capacity to advise women on health conditions and deliver services. Nurses recognized the increased capacity of community health workers and were more confident in their clinical and technological skills to identify women at risk of obstetric complications. Conclusions: Many of the community health workers reported that POM improved knowledge, self-efficacy and strengthened relationships with the communities they serve and local nurses. This helped to strengthen the link between community and health facility. However, findings highlight the need to consider program and systematic challenges to implementation.